2010
DOI: 10.1523/jneurosci.0340-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

L-3-n-Butylphthalide Improves Cognitive Impairment and Reduces Amyloid-  in a Transgenic Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is an age-related, progressive neurodegenerative disorder that occurs gradually and results in memory, behavior, and personality changes. L-3-n-butylphthalide (L-NBP), an extract from seeds of Apium graveolens Linn (Chinese celery), has been demonstrated to have neuroprotective effects on ischemic, vascular dementia, and amyloid-␤ (A␤)-infused animal models. In the current study, we examined the effects of L-NBP on learning and memory in a triple-transgenic AD mouse model (3xTg-AD) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 55 publications
3
82
0
Order By: Relevance
“…Generally, it was found that anti-oxidant treatment or activation of anti-oxidative pathways improve brain functions and partially restores age-dependent changes in gene expression both in normal ageing [87,88] and in models of accelerated ageing [89,90]. Clinical data suggest that dietary anti-oxidants have some protective effects against AD, Parkinson's disease and amyotrophic lateral sclerosis [91] and also in pharmacological and genetic models of neurodegenerative disorders [92][93][94]. We have to note that ROS have an important intracellular signalling function: oxidative stress responses may regulate autophagy and induce synaptic growth [95,96] suggesting that long-lasting diminished ROS production by pharmacological treatment could have a negative impact on brain functions.…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…Generally, it was found that anti-oxidant treatment or activation of anti-oxidative pathways improve brain functions and partially restores age-dependent changes in gene expression both in normal ageing [87,88] and in models of accelerated ageing [89,90]. Clinical data suggest that dietary anti-oxidants have some protective effects against AD, Parkinson's disease and amyotrophic lateral sclerosis [91] and also in pharmacological and genetic models of neurodegenerative disorders [92][93][94]. We have to note that ROS have an important intracellular signalling function: oxidative stress responses may regulate autophagy and induce synaptic growth [95,96] suggesting that long-lasting diminished ROS production by pharmacological treatment could have a negative impact on brain functions.…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…It is likely that aAPPs derived from dl-PHPB-mediated APP processing may serve as neuroprotective agents and contribute to the long-term benefit of dl-PHPB on memory in APP/PS1 mice. In addition, our previous study demonstrated that 3-nbutylphthalide (NBP) isoform could regulate APP processing and lowered Ab generation in AD mouse models (Peng et al, 2010. It has been demonstrated that Thr668-phosphorylated APP was significantly increased in AD brains.…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemistry was performed using the ELITE ABC method (Vector Laboratories, Burlingame, CA) as previously described (Peng et al, 2010). Ten-micron sagittal cryosections of mouse brain were mounted on glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…(Chang, Wang, 2003). L-NBP has been shown to reduce β-amylase-induced neuronal apoptosis and to improve cognitive function in Alzheimer's disease animal models (Peng et al, 2009;Peng et al, 2012;Peng et al, 2010;Peng et al, 2008;Xiang et al, 2014). Additionally, L-NBP has been demonstrated to ameliorate cognitive deficits and neuronal loss in the hippocampus of mice exposed to repetitive cerebral ischemia and reperfusion (Huai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%